From rationality to equality - Sterba, James P. (Oxford : Oxford University Press, 2013)
James P. Sterba offers something that philosophers have long sought: an argument showing that morality is rationally required. Furthermore he argues that morality requires substantial equality. Even libertarian perspectives, which would seem to require minimal enforcement of morality, are shown to lead to a requirement of equality.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes bibliographical references and index.
Keywords: Ethics; Equality